Improving the quality and quantity of clinical and translational research statewide: An application of group concept mapping - Jacquelyn Fede; Stephen J. Kogut; Anthony Hayward; John F. Stevenson; Cynthia Willey-Temkin; Heather Fournier; Gabrielle Stranieri; Judy A. Kimberly; James Padbury (Journal of Clinical and Translational Science, 2021)
Abstract